PENGARUH KEJELASAN SASARAN ANGGARAN, SISTEM PENGENDALIAN INTERN, DAN DESENTRALISASI TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris Pada SKPD Kabupaten Pasaman) - Aini, Nur Atika; Taufik, Taufeni; Hariyani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the influence of empirical evidence budget goal clarity, internal control system and decentralization the performance of local government officials Pasaman regency. This research was conducted by using a survey of local work unit Pasaman. The population in this study is 31 working units Pasaman. Samples taken amounted to 93 respondents. The type of data used are primary data with data collection method using a questionnaire. Data analysis method used in this study. The results showed that the Budget Targets Clarity significant effect on the performance of local governments with a regression coefficient of 0.748 with 0.001 significance (alpha 0.05), Internal Control System have a significant effect on the performance of local governments with a regression coefficient of 0.182 with 0.000 significance (alpha 0.05), Decentralization significantly affect the performance of local governments with a regression coefficient of 0.351 with 0.000 significance (alpha 0.05). With a total number of (Adjusted R²) square value of 0.450, which means by 45.0%. While the remaining 55.0% influenced by other variables not included in the regression models were not included in this study as organizational commitment, participation budgeting and others.Keywords: Performance, governments, budget, internal control systems, and decentralization